Patients with III and IV category of the Bethesda System under levothyroxine non-suppressive therapy have a lower rate of thyroid malignancy - Kaliszewski, Krzysztof (Sci Rep, 2019)
Thyroid nodules (TNs) assigned to the Bethesda System categories III and IV include numerous clinical characteristics, which increase or decrease the risk of malignancy. However, there are very few data regarding the influence of TSH non-suppressive thyroid hormone therapy (NSTHT) on the risk of malignancy in patients in the aforementioned categories. We assessed the number of patients with thyroid nodules assigned to categories III and IV who take TSH NSTHT and if thyroid hormone therapy is associated with a rate of malignancy. We retrospectively analyzed the medical records of 4,716 individuals and selected 532 (11.28%) patients with Bethesda System category III and IV thyroid nodules. All participants underwent surgery, and histopathological verification was obtained in all cases. In all, 33.1% of individuals with category III and IV thyroid nodules took TSH NSTHT. In patients with category III nodules, application of NSTHT was associated with a lower rate of thyroid cancer (TC), though this observation was not significant (OR = 0.55, p = 0.381). In patients with category IV nodules, we demonstrated a significantly lower rate of TC when NSTHT was applied (OR = 0.44, p = 0.005). In conclusion, the prevalence of patients with Bethesda System category III and IV thyroid nodules who take NSTHT is high. TSH NSTHT significantly decreases a rate of malignancy in category IV, but not category III patients.